THE EFFECTIVENESS OF STORY COMPLETION TECHNIQUES ON STUDENTS' SPEAKING SKILL AT SMA NEGERI 1 ARALLE (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study targets to decide using tale crowning glory strategies in enhancing the talking skills of second grade college students of SMAN 1 Aralle. The impartial variable of this research is the Story Completion Technique and the established variable is the college students' talking skill. This examine makes use of a pre-experiment in which the pre-experiment methods are pre-test and post-test. In the pre-test, college students are given a test. This is an oral test earlier than giving remedy. In the post-test, college students are given a test, as with inside the pre-test, which is a test to find out the results of the remedy that has been given. In the remedy, college students get material about the completion of the story. The subjects of this study were students of class X SMAN 1 Aralle, totaling 38 college students. The improvement of students' talking skills by using story-solving techniques can be seen in the post-test ratings after giving gifts. After being given treatment, the student's rating (post-test) changed into higher than the student's rating (pre-test) earlier than being given remedy. The imply rating of the students' pre-test was 44.37 which was categories as poor. And the average post-test rating of college students is 61.95 which is classified as good. Students' speaking skills increased significantly by looking at the paired sample test, which was 0.00 decrease than the price of 0.05, because of this that the null hypothesis (H0) is rejected and the opportunity hypothesis (H1) is accepted. Based at the findings and dialogue of the studies, it is able to be concluded that using tale crowning glory is powerful to enhance college students' talking talents at SMAN 1 Aralle.